Pengaruh Harga, Produk dan Kualitas Pelayanan terhadap Keputusan Pembelian dalam Berbelanja Buah Lokal di Supermarket Gelael - Rayhan, Muhammad; Putra, Suadi Sapta; Digdowiseiso, Kumba (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This study aims to determine the effect of price, product and service quality on purchasing decisions in shopping for local fruit at Gelael Supermarket Jakarta. This research is a quantitative descriptive analysis research. The source of this research data was given to 100 respondents aged 15-55 years and had shopped at the Gelael supermarket at least once. In taking the sample in this study using purposive sampling technique. The data sources of this study used data analysis techniques, namely, multiple linear regression and hypothesis testing using SPSS 21 to test the regression coefficients. From the research subjects of 100 respondents, most of the research subjects were dominated by the female gender (62%) while the work was dominated by students (59%) and the income was dominated by 0 – 2,000,000. The results of this study indicate that there is an influence between price (X1) on purchasing decisions (Y) of 0.385 and has a large influence of 3.85%. For the Product variable (X2) on the Purchase Decision (Y) of 0.217 and has an influence of 2.17%. For the service quality variable (X3), it is 0.300 and has an effect of 3.00%. Partially or simultaneously have a strong influence among the three variables, the most significant is the variable Price (X1) of 0.000. The results of this study expect satisfaction to increase the price (X1) which can support the purchase decision.